Formation of the teacher’s professional culture in the context of pedagogy of success - Андрєєв, М. В.; Маркова, В. М. (Scientific notes of the pedagogical department, 2020)
The article deals with the problem of forming the professional culture of a teacher, capable of carrying out the educational process in the establishment of secondary education at a high quality level in the context of the implementation of the principles of pedagogy of success. The authors have found out the essence of the concept “pedagogical culture” and have justified its influence on the success of teacher’s professional activity. On the basis of the best practices of classical pedagogy and the researches of modern scientists, the criteria and indicators of professionalism of the successful teacher are emphasized distinguished. Moreover, the evaluation of his/her professional competence are considered, as a condition of becoming and development of teacher-master and as a component of the content of pedagogical culture. Based on the scientific generalizations and the results of empirical researches, the main features of per- sonality-oriented pedagogical culture are distinguished. The influence of individual pedagogical culture’s components on the teacher’s education are indicated. In this article, the components of the level of pedagogical culture of the teacher are represented. The results of the profile and questionnaire of the expert teachers of the establishments of secondary education give opportunity to determine an important connection between the level of teacher’s culture and the success of his/her professional activity. This connection has been demonstrated according to distinguishing criteria using the table of combination and Pearson’s correlation coeﬃcient.